Beyond brand fit: The influence of brand contribution on the relationship between service brand alliances and their parent brands. (3rd June 2019) - Su, Yiran; Kunkel, Thilo
Abstract : Purpose: The purpose of this paper is to examine the underlying mechanism of the spillover effect from a service brand alliance to its parent brand at the post-consumption stage. Design/methodology/approach: Online surveys were used to collect both qualitative and quantitative data from participants of an actual event. Conceptual models were developed and tested on two cross-sectional samples using structural equation modeling. Findings: Results demonstrate perceived brand contribution and consumer involvement mediate the relationship between the service brand alliance experience and the evaluation of its parent brand at the post-consumption stage. While perceived brand fit had an indirect effect on the parent brand, the spillover was mostly driven by service alliance experience and perceived brand contribution. Practical implications: Findings indicate brand managers should focus on consumers' brand experience of the service brand alliance to drive spillover evaluations to the parent brand, and organizations could extend brand alliances to services with low category fit to the parent brand if consumers are to have a good experience with the service brand alliance. Originality/value: This research extends findings on brand alliance research that was based on hypothetical brands and indicated that the spillover effect from a brand alliance to the parent brand is influenced by perceived brand fit. The findings highlight the importance of consumer experiences in driving the spillover effect at the post-consumption stage, where consumers evaluate brand relationships from a value-added perspective that goes beyond the service category fit.